A Long-Lasting Phosphor Ba3P4O13: Eu2+. (13th November 2014) - Guo, Haijie; Chen, Wenbo; Zeng, Wei; Wang, Yuhua; Li, Yanyan
Abstract : A new long-lasting phosphor Ba3 P4 O13 : Eu 2+ has been synthesized through the high temperature solid-state method. The excitation spectrum of Ba2.99 P4 O13 : 0.01Eu 2+ is a broadband from 200 to 450 nm attributed to the 4f 7 →4f 6 5d 1 transition of Eu 2+ ions. The emission spectrum of Ba2.99 P4 O13 : 0.01Eu 2+ exhibits an asymmetric emission band ascribed to the 4f 6 5d 1 →4f 7 transition of Eu 2+ ions in two different sites. Under the optimum doping concentration, the long-lasting phosphorescence (LLP) can persist for nearly 85 min at recognizable intensity level (≥0.32 mcd/m 2 ). The mechanism of afterglow is discussed briefly.